Does Innovation Stimulate Employment? A Firm-Level Analysis Using Comparable Micro-Data From Four European Countries - Rupert Harrison; Jordi Jaumandreu Balanzo; Jacques Mairesse; Bettina Peters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper studies the impact of process and product innovations introduced by firms on employment growth in these firms. A simple model that relates employment growth to process innovations and to the growth of sales separately due to innovative and unchanged products is developed and estimated using comparable firm-level data from France, Germany, Spain and the UK. Results show that displacement effects induced by productivity growth in the production of old products are large, while those associated with process innovations, which are likely to be compensated by price decreases, appear to be small. The effects related to product innovations are, however, strong enough to overcompensate these displacement effects.
Keywords: J23; L1; O31; O33; D2; 330; Innovation; employment; community innovation surveys; Innovation; Unternehmensentwicklung; Beschäftigungseffekt; Frankreich; Deutschland; Spanien; Großbritannien